Velocity gradient of the floor exercise - Petrova, M.; Dimitrova, B. (Journal of Applied Sports Sciences, 2019)
The methodological classification of the volume of the exercises is in the basis of the multi-annual preparation in gymnastics. A number of authors (Dimitrova, 2015; Borisenko, 2000; Fisenko, 2005; Gaverdovskiy, Smolevskiy, 2014) note that for the apparatus of female all around - balance beam and floor exercise, the volume material united in different structural groups isequal. The basic motor habits differ only as regards the specificity of the particular apparatus.The aim of the research is to establish the role of the velocity gradient for the learning algo-rithm in a multi-annual aspect and on floor exercise. We used kinematic analysis, comparative data analysis and variation analysis when we processed the results. The analysis of the results allowed us to establish the role of the velocity gradient for learning algorithm in the multian-nual aspect and of floor exercise. Our research has shown that the basic exercises sequence on floor exercise according to the gradient velocity does not fully correspond to the methodical sequence of training used for years so far. We established the following dependence: the greater number of movements in the main action phase executed for shorter time increases the velocity gradient. It was confirmed for the apparatuses of the gymnastic all around too. The obtained values for the velocity of basic exercises of floor exercise by structural group confirmed their direct proportional dependence on difficulty